Abonamiento con dosis de gallinaza y su influencia en las características agronómicas y rendimiento de Brassica juncea L. “mostaza de hoja”, en Zungarococha, provincia de Maynas-Loreto.2021 - Andrade Fumachi, Joyce Karol (2022)
The experiment was carried out at the facilities of the Workshop on Teaching and Research of Horticultural Plants (TEIPH), of the Faculty of Agronomy-UNAP, located at Km. 3 of the Zungarococha road, south of the city of Iquitos, whose geographical coordinates are: South Latitude 03o 46 x 13.2; West Length 73o 22 x 10.4; Elevation: 126 meters above sea level. The type of research was quantitative, experimental, explanatory, transversal and prospective, with an independent variable (Hen dose) and seven dependent variables (Plant height, plant diameter, root length, number of leaves/plant, leaf/plant weight, total plant weight and leaf weight/ha). The objective of the research work was to determine whether the payment with hen dose influences the agronomic characteristics and yield of Brassica juncea L. "Leaf mustard", in Zungarococha, Maynas-Loreto Province.2021. For the purpose of statistical analysis, Completely Random Block Design was used, with 4 Treatments and 4 repetitions. Each experimental unit consisted of 3 rows, 8 plants/row and the sampling unit consisted of 4 plants/experimental unit. According to the results obtained, the following conclusions were had: Hen doses in Brassica juncea L. "leaf mustard" influenced agronomic characteristics and yield. Treatment T4 (60 t of hen/ha), presented the highest average values of agronomic characteristics and crop yield where it obtained 45,933.56 kg of leaves/ha and with an economic income of S/.32,766.56.